STRATEGI PENGEMBANGAN BISNIS USAHA KEY DIGITAL : SEBUAH APLIKASI LAYANAN PEMBELIAN PULSA MURAH DAN MUDAH: APLIKASI LAYANAN PEMBELIAN PULSA MURAH DAN MUDAH - Sucayono; Ayu Mustikaningsih (JEKOS (Jurnal Ekonomi Dan Sosial), 2025)
The development of digital technology has driven the growth of application-based businesses, including in the prepaid credit (pulsa) purchasing sector. Key Digital is one of the MSMEs operating in the provision of affordable and easy-to-access services for purchasing phone credit, data packages, and other digital products. This study aims to identify the business development strategy of Key Digital using the SWOT approach. The research method used is descriptive qualitative, with data collected through interviews, observations, and documentation. The analysis results show that Key Digital has strengths in operational efficiency and competitive pricing but has weaknesses in brand awareness and marketing scale. The development strategies include utilizing social media, strengthening partnerships, and innovating app features. Keywords: Development Strategy, SWOT, Phone Credit App Management.